Medical Information Services in the Netherlands - Bakker, Suzanne (Igaku Toshokan, 1996)
This article gives a brief description of the library organization in the Netherlands with emphasis on medical libraries. Library automation and cooperation is dominated by the PICA system (Project Integrated Catalogue Automation), a system which is used for shared cataloguing and interlibrary loan requests. The largest collection of periodicals in the sciences, life sciences and medicine in the Netherlands is found in the library of the Royal Netherlands Academy of Sciences. Second best are the libraries of the eight medical faculties in the Netherlands. Several health care institutes and organizations have important and specialized library collections. Library education in the Netherlands is either an in-service training with part-time theoretical courses or a four-year program in higher education. The biomedical information group of the Dutch Association of Librarians is well organized and very active. Task forces and study groups are working on several subjects, e. g. library automation, job descriptions, quality management, minimal requirements for medical libraries, internet sources and continuing education. The main issues in the next few years will be further development and integration of computer facilities together with library services. For most libraries finances will make it impossible to keep the collection of books and journals up-to-date and to maintain size and quality of the printed collection. Therefore pricing of document delivery, interlibrary loans, copyright, bibliographic and full-text databases will set constraints to information services where automation and networking promise potentially unlimited possibilities.